THE EFFECT OF ORGANIZATIONAL CLIMATE AND EMPOWERMENT ON EMPLOYEE COMMITMENT AT THE HEAD OFFICE OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE - Kartasasmita, Hendra Hafiz; Rangkuti, Zulkifli; Jati, Prihatina (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This research has a quantitative approach, descriptive and associative type. In this research, the author narrowed the population, namely the number of civil servant employees at the Ministry of Trade Office to 447 employees by calculating the sample size using the Slovin technique, so the number of samples studied was 82 respondents, namely civil servants at the Head Office of the Directorate General of Customs and Excise. The results of this research show that: 1) There is an influence of Organizational Climate on Employee Commitment, as evidenced by the tcount value for the Organizational Climate variable (X1) of 6,171 while the ttable value for n = 82 is 1,989. So 6,171 > 1,989, then H0 is rejected and Ha is accepted, it can be stated that Organizational Climate (X1) has a significant effect on Employee Commitment (Y). 2) There is an influence of Empowerment on Employee Commitment, as proven by the tcount value for the Empowerment variable (X2) of 6,376, while the ttable value for n = 82 is 1,989. So 6,376 > 1,989, then H0 is rejected and Ha is accepted, it can be concluded that partially the Empowerment variable (X2) has an effect on Employee Commitment (Y). 3) There is an influence of Organizational Climate and Empowerment together on Employee Commitment. It is proven from the ANOVA test that the Fcount value is 70.213, while the Ftable (a 0.05) for n = 82 is 2.72. So Fcount > from Ftable (a 0.05) or 70.213 > 2.72 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Organizational Climate (X1) and Empowerment (X2) together or simultaneously have a positive effect on Employee Commitment (Y ), with an R Square value of 0.640. This shows that 64.0% of Organizational Climate (X1) and Empowerment (X2) together influence Employee Commitment (Y), while the remaining 36.0% is influenced by other factors not examined in this research